Aplicación de las estrategias del diseño integral a una propuesta de creación de marca y productos comunicacionales para los artesanos de la paja toquilla ecuatoriana de Montecristi - Kim Kim, Sam Minsoo (2013)
Through this research project created a brand and communications products for craftsmen Ecuadorian Montecristi straw shawl. Was made to the craftsman make use of them in a local or international market, using the benefits of the hat in favor of them and not been doing previously calling Panama hat. The purpose is to increase the taxes of Fame hat, the hat is considered a source working for many families in different communities, and also avoid the hat is extinguished. The website was created to promote the brand; it also means that the craftsman will have the opportunity to sell abroad, taking advantage of all the benefits themselves, without the need for an intermediary. The photo book is a promotional product that will allow the customer values the craftsmanship. Artwork as: poster, flyers, brochures... to promote the work of the artisan. The catalog will contain photos of different models of hats, in which the customer can choose the model you want. The basic stationery: letter format, folder labels, physical and electronic bills.